A New Class Of Nearly Open Sets In Nanotopological Spaces - Ms. J. Arul Jesti, Ms. K.Heartlin (International Journal of Advanced Science and Technology, 2020)
The aim of this paper is to introduce a new class of sets, namely Nano semi*-open sets and Nano semi*-closed sets. Further we define Nano semi*-interior and Nano semi*-closure  and discuss its properties. Additionally we relate Nano semi*-open sets and Nano semi*-closed sets with some other sets.